2020
DOI: 10.1029/2019gl085598
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and Upper Mantle Shear Wave Velocity Structure of Botswana: The 3 April 2017 Central Botswana Earthquake Linked to the East African Rift System

Abstract: Rayleigh wave group and phase velocity measurements obtained from ambient noise and earthquake data at 51 broadband stations were used to construct the first 3‐D crustal and upper mantle shear wave velocity model of Botswana. The model shows low crustal velocities associated with the Passarge and Nosop sedimentary basins, whereas the Kaapvaal, Zimbabwe, Maltahohe, and Congo Cratons are recognized by high mantle velocities. The lowest upper mantle shear wave velocity, beneath northeastern Botswana, is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…Thick lithosphere beneath the Kalahari Craton is revealed with an average thickness of 242 ± 39 km, which is comparable to values of about 220 km from magnetotelluric (MT) inversions (e.g., Evans et al, 2011; Miensopust et al, 2011; Muller et al, 2009) and ~200 km or greater determined from a recent surface wave tomography study (Fadel et al, 2020). Both the southern Rehoboth Province (241 ± 35 km) and the Magondi Belt (251 ± 41 km) have a lithospheric thickness that is comparable with that of the Kalahari Craton, an observation that is consistent with the suggestion that both areas represent the westward extension of cratonic lithosphere based on craton‐like high‐velocity anomalies (Ortiz et al, 2019) and similar electrical structure (Muller et al, 2009).…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Thick lithosphere beneath the Kalahari Craton is revealed with an average thickness of 242 ± 39 km, which is comparable to values of about 220 km from magnetotelluric (MT) inversions (e.g., Evans et al, 2011; Miensopust et al, 2011; Muller et al, 2009) and ~200 km or greater determined from a recent surface wave tomography study (Fadel et al, 2020). Both the southern Rehoboth Province (241 ± 35 km) and the Magondi Belt (251 ± 41 km) have a lithospheric thickness that is comparable with that of the Kalahari Craton, an observation that is consistent with the suggestion that both areas represent the westward extension of cratonic lithosphere based on craton‐like high‐velocity anomalies (Ortiz et al, 2019) and similar electrical structure (Muller et al, 2009).…”
Section: Resultssupporting
confidence: 67%
“…This observation, together with results from other studies using the SAFARI data, including minor (≤ ~5 km) crustal thinning (Fadel et al, 2018; Yu, Liu, Reed, et al, 2015), absence of rifting‐related mantle flow field as revealed by shear wave splitting analysis (Yu, Gao, et al, 2015), and small (~ −1%) velocity anomalies in the upper mantle directly beneath the rift zone compared to other continental rifts (Yu et al, 2017), is inconsistent with the hypothesis that active mantle upwelling plays a major role in rift initiation. Minor mantle velocity anomalies associated with the ORZ are also suggested by recent body (Ortiz et al, 2019) and surface wave (Fadel et al, 2020) seismic tomography studies utilizing the same data set that is used for MTZ discontinuity imaging in this study.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations